2013
DOI: 10.1186/1743-8977-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the mechanisms of cellular uptake of engineered nanoparticles by accurate evaluation of internalization using imaging flow cytometry

Abstract: BackgroundThe uptake of nanoparticles (NPs) by cells remains to be better characterized in order to understand the mechanisms of potential NP toxicity as well as for a reliable risk assessment. Real NP uptake is still difficult to evaluate because of the adsorption of NPs on the cellular surface.ResultsHere we used two approaches to distinguish adsorbed fluorescently labeled NPs from the internalized ones. The extracellular fluorescence was either quenched by Trypan Blue or the uptake was analyzed using imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 47 publications
3
130
0
1
Order By: Relevance
“…Nonetheless, flow imaging based assays, similar to conventional flow cytometric assays, are able to incorporate additional read outs such as staining for markers of immune activation and function thereby allowing direct associations to be made between TiO 2 interactions with single cells (adhesion or internalization) and the functional consequences of such interactions on the same cell. Like others, we found imaging cytometry a powerful technique for the analysis of particle localization, this was dependant on tailoring custom masks in order to obtain an accurate analysis 9, 10, 11, 12, 13, 14, 15. There is always potential for some particles analyzed to be attached externally to the front or back of the cells, the occurrence of false positive internalization events is random and at the same frequency within all data files as it is dependent only on the orientation of the cells as they are imaged.…”
Section: Discussionmentioning
confidence: 68%
“…Nonetheless, flow imaging based assays, similar to conventional flow cytometric assays, are able to incorporate additional read outs such as staining for markers of immune activation and function thereby allowing direct associations to be made between TiO 2 interactions with single cells (adhesion or internalization) and the functional consequences of such interactions on the same cell. Like others, we found imaging cytometry a powerful technique for the analysis of particle localization, this was dependant on tailoring custom masks in order to obtain an accurate analysis 9, 10, 11, 12, 13, 14, 15. There is always potential for some particles analyzed to be attached externally to the front or back of the cells, the occurrence of false positive internalization events is random and at the same frequency within all data files as it is dependent only on the orientation of the cells as they are imaged.…”
Section: Discussionmentioning
confidence: 68%
“…These results indicated that the uptake of NPs in muscle cells was mainly an energy-dependent process, as observed in various cell types, including pancreatic, hepatic, and epithelial cells. 26,[29][30][31] In addition, even though ATP depletion considerably reduced NP uptake, it is not impossible that NPs enter cells via ATPindependent processes, as already proposed. 32,33 Accordingly, a physicochemical mechanism involving adhesion and membrane spreading around the NP surface has already been observed, with large unilamellar liposomes and red blood cells both lacking endocytic capabilities.…”
Section: Internalization Pathways Of Nps Within C2c12 Cellsmentioning
confidence: 74%
“…26 Shortly, the synthesis was based on the method described by Van Blaaderen. 27 In a first step, FITC (Thermo Fisher Scientific, Rockford, IL, USA) was covalently attached to a silane-coupling agent, (3-aminopropy1)triethoxysilane (APS), by the reaction of an amino group with an isothiocyanate group, leading to a thiourea link.…”
Section: Nanoparticle Synthesismentioning
confidence: 99%
“…Recently, SS signal analysis was successfully applied for detecting carboxylated nanodiamonds and tungsten carbide‐cobalt (WC‐Co) NMs in cells, results being validated by Raman and confocal microscopy associated with 3D reconstruction 82, 83. Finally, imaging flow cytometry (an integrative approach combining flow cytometry analyses with confocal microscopy) relates the physicochemical characteristics of NMs to their uptake, with a view to designing safe NMs 84. Flow cytometry appears to be a good alternative method to detect NM internalization compared to TEM which is very time‐consuming and requires heavy equipment.…”
Section: High‐throughput Flow Cytometrymentioning
confidence: 99%